2009
DOI: 10.1177/1462474508098132
|View full text |Cite
|
Sign up to set email alerts
|

Anger about crime and support for punitive criminal justice policies

Abstract: Previous research on the sources of punitive attitudes has largely focused on the cognitive and demographic factors associated with the desire to punish criminals harshly. This study focuses on the link between affect and punitiveness by examining the relationship between anger about crime and support for punitive criminal penalties. Using national survey data from the USA, this research shows that anger about crime is a significant predictor of punitive attitudes, after controlling for other factors such as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(186 citation statements)
references
References 52 publications
11
147
2
6
Order By: Relevance
“…This study tests the assumption that both types are associated with punitivity in different ways. Furthermore, Johnson (2009) showed that anger over crime works in a different way than fear of crime in predicting individuals' level of punitivity.…”
Section: Fear Of Crimementioning
confidence: 99%
See 3 more Smart Citations
“…This study tests the assumption that both types are associated with punitivity in different ways. Furthermore, Johnson (2009) showed that anger over crime works in a different way than fear of crime in predicting individuals' level of punitivity.…”
Section: Fear Of Crimementioning
confidence: 99%
“…Several studies use different indicator variables to build a measurement index (Chiricos et al 2004: 369;Hartnagel and Templeton 2012: 460;Hogan et al 2005: 399;Hirtenlehner 2011: 37;Johnson 2009;Kury and Obergfell-Fuchs 2008: 242;Windzio et al 2007: 45, Hough et al 2013. However, few studies investigate whether the response to a series of opinion questions on criminal policy really originates from a common underlying conviction (punitivity), and most of them are based on data from surveys in the US (Mascini andHoutman 2006, Pickett andBaker 2014).…”
Section: Punitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The liberal political left, on the other hand, thinks that the causes of crime can be found in structural economical inequalities and problems of discrimination; the solution lies in reforming the system and rehabilitating offenders. Support for harsh sentencing of criminals thus seems to be a right-wing phenomenon: conservatives tend to be more punitive towards offenders than liberals (Carroll et al, 1987;Hogan et al, 2005;Johnson, 2009;King & Maruna, 2009;Miller, 1973;Tetlock et al, 2007;Tyler & Boeckmann, 1997).…”
Section: On the Ideological Foundations Of Punitive Sentimentmentioning
confidence: 99%